Route Optimization for Delivery Vehicles in International Road Transport - Tumielewicz, Michał; Lemański, Dominik (Towards Sustainable Transport in Logistics and International Trade, 2025)
The aim of this chapter is to compare various international road transport route options for vehicles with a maximum permissible weight of up to 3.5 tons, taking into account legal regulations, travel time, fuel consumption, and handling of intermediate points. The research methodology was based on the analysis of two routes: a direct one (Łódź–Amsterdam) and a route with intermediate stops (Bydgoszcz, Poznań, Hamburg). The results indicate that the most efficient solutions are either the shorter direct route or the variant with intermediate points where the first loading takes place in Bydgoszcz. A limitation of the study is the use of theoretical data without accounting for random variables (e.g., traffic jams, breakdowns). The practical implications include streamlining route planning and increasing the operational efficiency of carriers. The value of the chapter lies in providing an analytical tool for optimizing road transport at the international level, while considering real legal and logistical conditions.